2018
DOI: 10.24926/iip.v9i4.1394
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Pharmacy Internship: A Toolbox for Success

Abstract: Objective: To describe available compensated student internships and provide guidance for new program development. Methods:  A search was conducted using PubMed, MEDLINE, and Google with the following search terms: pharmacy, intern, internship, and student.  All English language publications were considered for inclusion.  Articles describing IPPE or APPE student utilization were excluded. Key findings: Pharmacy student internship programs are common in practice, though there are few with pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“… 6 In the same issue, they published a toolkit with suggestions on how to design, implement, and assess student internship programs. 7 The present study is in response to this call and designed with suggested concepts and innovations.…”
Section: Description Of the Problemmentioning
confidence: 99%
“… 6 In the same issue, they published a toolkit with suggestions on how to design, implement, and assess student internship programs. 7 The present study is in response to this call and designed with suggested concepts and innovations.…”
Section: Description Of the Problemmentioning
confidence: 99%
“…Measuring a cost-analysis for the program, tracking research accomplishments of participants, and identifying direct patient care activities completed are just a few examples of metrics highlighted in the toolbox provided in this issue. 5 Additionally, analyzing direct patient care pharmacist activities that highly integrated interns are able to accomplish could showcase the downstream effects of a wellrun program. Whatever you define as outcomes for program success, make sure you capture those outcomes and reflect on needed changes.…”
Section: Continuous Quality Improvementmentioning
confidence: 99%
“…Too often, pharmacy interns primarily fill a technical or distributive need within the pharmacy department, simply shadow pharmacists, and fail to be utilized to their fullest potential. The complementary toolbox in this issue 5 summarizes the sparse literature surrounding student internships and their role within the profession. We suggest the following considerations to utilize interns as pharmacist extenders, expand the reach of our profession, and build leaders.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the internship process, the final product or result, usually in the written form of an internship report, seems to us worthy of further analysis that goes beyond the various casuistic normative formulations, but which may vary greatly (Ellis and Childs, 2019) either from one institution to another (Nisly et al, 2018) or in the area of scientific training and in the trainees", mentors" and host institutions" standpoint. Furthermore, it should be taken into account that "The issue of influence of mentoring style to the development of mentees" pedagogical and didactic competencies is still not sufficiently investigated" (Ciučiulkienė and Mičiulienė, 2019) and that "Mentoring is a process when a more qualified and experienced person teaches, supports, promotes, advises" (p. 131).…”
Section: Introductionmentioning
confidence: 99%